PEMANFAATAN SARANA PEMBELAJARAN OLEH GURU DALAM PENINGKATAN MUTU PEMBELAJARAN - Yuyum Surtini (Jurnal Tata Kelola Pendidikan, 2021)
This study entitled "The Utilization of Learning Facilities by Teachers in Improving the Quality of Learning in SMA Negeri 3 Kota Serang" . In the learning process, facilities and infrastructure are indispensable for schools to support the success of learning activities. The availability and utilization of relevant facilities and infrastructure is needed so that all educational activities in schools can be achieved effectively and efficiently. The purpose of this study was to determine the condition of learning facilities and describe the use of existing learning facilities in SMA Negeri 3 Kota Serang. The method used in this study is a qualitative research method with a pende type descriptive words. The subjects in this study were the deputy head of facilities and infrastructure, teachers and students. The data obtained in the field were analyzed data to obtain research findings. Data collection was carried out by observation, interviews and documentation. Test data validity with data credibility and confirmability. The results of this research and discussion indicate that: the learning facilities at SMA Negeri 3 Kota Serang are good enough according to existing standards. However, there are a number of facilities that are still not up to standard. Meanwhile, the use of learning facilities by teachers at SMA Negeri 3 Kota Serang has not been optimal. Most of the teachers have not used learning tools and media during the process of teaching and learning activities and some are still in the level of trying to use them. Pe Utilization means the learning process remains to be improved, as improving the quality of learning on an ongoing basis to meet the realities and expectations for the customer.